2014
DOI: 10.1186/1556-276x-9-17
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the role of the molecular weight of polyvinyl pyrrolidone in the shape control of high-yield silver nanospheres and nanowires

Abstract: Serving as shape control agent, polyvinyl pyrrolidone (PVP) has been widely used in chemical synthesis of metal nanoparticles. However, the role of molecular weight (MW) of PVP has been rarely concerned. In this study, we show a facile method to control the shapes of silver nanocrystals using PVP with different MWs. PVPMW=8,000, PVPMW=29,000, PVPMW=40,000, and PVPMW=1,300,000 are compared in the present study. Surprisingly, high-yield silver rodlike nanostructures, nanospheres, and nanowires can be obtained un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(87 citation statements)
references
References 35 publications
1
85
0
1
Order By: Relevance
“…We used a convenient and fast approach for synthesis of silver nanowires based on the work published by Song et al [12], and the preparation process is shown in Figure 1. In a synthesis process, 1 ml AgNO 3 solution (0.9 M in EG) and 0.6 ml NaCl solution (0.01 M in EG) were quickly put into 18.4 ml PVP solution (0.286 M in EG).…”
Section: Methodsmentioning
confidence: 99%
“…We used a convenient and fast approach for synthesis of silver nanowires based on the work published by Song et al [12], and the preparation process is shown in Figure 1. In a synthesis process, 1 ml AgNO 3 solution (0.9 M in EG) and 0.6 ml NaCl solution (0.01 M in EG) were quickly put into 18.4 ml PVP solution (0.286 M in EG).…”
Section: Methodsmentioning
confidence: 99%
“…Influence of PVP on the Yield and Dimensional Properties of Cu NWs. The molecular weight and concentration of PVP have been reported to control the yield and dimensions of NWs [36][37][38][39] due to their preferential adsorption on {100} planes of metallic surface compared to {111}. Thus, the effect of PVP concentration on the synthesis of Cu NWs at the reaction temperature of 182°C is investigated, while keeping Cl − /Cu 2+ molar ratio and the amount of N 2 purged constant.…”
Section: Influence Of Halide Ion Source and Its Concentration Onmentioning
confidence: 99%
“…In addition, PVP molecules are reported to enhance the reduction of metal salts by forming complexes through coordination between metallic ions and C=O groups and also stabilize the products subsequently [36,37]. However, the specific adsorption of PVP for the unidirectional growth of metallic seeds is only realized at specific Cl − ion concentrations [28,36,40]. At conditions suitable for the reduction of Ag ions to metallic Ag, Cl − ions control the morphology of Ag products through the etching processes that generate multitwinned Ag seeds.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high thermal and electrical conductivity of bulk silver, it is one of the most promising metal nanowire materials. [1][2][3][4][5][6][7][8] Silver nanowires hold promise as the conductive material in conductive inks suitable for screen printing. 8,[10][11][12][13][14][15] There are several methods to synthesize silver nanowires including the polyol process, hydrothermal synthesis, wet chemical process and irradiation photo reduction.…”
mentioning
confidence: 99%